Representation of Family Values in Wardah Ramadan Series YouTube Channel: Peirce Semantic Analysis Study on Mengalah untuk Melangkah Web Series - Nanik Mujiati; Dwi Ubaidillah Hidayat; Galuh Nuril Lathifah (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2025)
This research aims to understand the representation of family values in the web series titled